Sonerila bokorense (Melastomataceae), a new species from Cambodia - Cho, Seong-Hyun; Lee, Jung-Hoon; Won, Hyosig; Phourin, Chhang; Kim, Young-Dong (Phytotaxa, 2015)
Sonerila bokorense, a new species of Melastomataceae from Cambodia, is described and illustrated. The new species is similar to S. calophylla, but it is distinguished by having aggregated tubercles, narrower leaves, and glandular trichomes on the pedicels, hypanthium, mid-veins of abaxial petals, and capsules.